2016
DOI: 10.1158/1078-0432.ccr-15-1031
|View full text |Cite
|
Sign up to set email alerts
|

Detection of T790M, the Acquired Resistance EGFR Mutation, by Tumor Biopsy versus Noninvasive Blood-Based Analyses

Abstract: Purpose The T790M gatekeeper mutation in the Epidermal Growth Factor Receptor (EGFR) is acquired by some EGFR-mutant non-small cell lung cancers (NSCLC) as they become resistant to selective tyrosine kinase inhibitors (TKIs). As third generation EGFR TKIs that overcome T790M-associated resistance become available, noninvasive approaches to T790M detection will become critical to guide management. Experimental Design As part of a multi-institutional Stand-Up-To-Cancer collaboration, we performed an explorator… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
237
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 326 publications
(262 citation statements)
references
References 39 publications
17
237
2
2
Order By: Relevance
“…The EGFR T790M mutation was 74% concordant between CTCs and tumor biopsies, whereas the ctDNA was concordant with tumor biopsies in 61% of cases. When CTC and ctDNA genotyping were combined, the T790M mutation was detected in 100% of cases, with 35% detection in in patients that had a negative or indeterminate concurrent biopsy (52). While this study showed that using CTC for detection of the T790M mutation was feasible, the yield may be increased by the combination of multiple genotyping modalities.…”
Section: Predictivementioning
confidence: 75%
“…The EGFR T790M mutation was 74% concordant between CTCs and tumor biopsies, whereas the ctDNA was concordant with tumor biopsies in 61% of cases. When CTC and ctDNA genotyping were combined, the T790M mutation was detected in 100% of cases, with 35% detection in in patients that had a negative or indeterminate concurrent biopsy (52). While this study showed that using CTC for detection of the T790M mutation was feasible, the yield may be increased by the combination of multiple genotyping modalities.…”
Section: Predictivementioning
confidence: 75%
“…It was not possible to confirm concordance between plasma and re-biopsy. However, a previous study has reported the concordance between liquid biopsy (cell free plasma DNA and circulating tumor cell) and concurrent re-biopsy was ~60% (42). Considering this result, it is difficult to discuss the validity of liquid biopsy in comparison with re-biopsy.…”
Section: Discussionmentioning
confidence: 92%
“…Ein überaus wichtiger Punkt ist zudem, dass Resistenzmutationen im Plasma auch dann nachgewiesen werden können, wenn eine zeitgleiche Biopsie nicht möglich ist oder ein negatives Ergebnis liefert [96,97] …”
Section: Potenzielle Klinische Anwendungen Von Hochauflösenden Methodenunclassified